2022
DOI: 10.1002/jdn.10189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to fluoxetine on circadian rhythmicity in the locomotor activity and neuropeptide Y and 5‐HT expression in male and female adult Wistar rats

Abstract: Serotonin (5-HT) reuptake inhibitors, such as fluoxetine, are the most prescribed antidepressant for maternal depression. In this sense, it exposes mothers and the brains of infants to increased modulatory and trophic effects of serotonergic neurotransmission. 5-HT promotes essential brain changes throughout its development, which include neuron migration, differentiation and organisation of neural circuitries related to emotional, cognitive and circadian behavior. Early exposure to the SSRIs induces long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, previous studies reported no sex differences in the brain NPY mRNA (Hill et al 2014) or protein (Henn et al 2021;Carboni et al 2022;Linhares et al 2022) levels. With regards to the specific receptors mediating NPY transmission, the density of the cortical NPY receptors Y1 was higher in males, while their affinity was greater in females (Michel et al 1995).…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, previous studies reported no sex differences in the brain NPY mRNA (Hill et al 2014) or protein (Henn et al 2021;Carboni et al 2022;Linhares et al 2022) levels. With regards to the specific receptors mediating NPY transmission, the density of the cortical NPY receptors Y1 was higher in males, while their affinity was greater in females (Michel et al 1995).…”
Section: Discussionmentioning
confidence: 79%
“…However, as the rest-activity rhythm does not perform like a cosine function [ 62 ], other non-parametric variables were needed as IS, IV, L5, and M10 to see locomotor activity in detail [ 60 ]. Although M10 and L5 are based on rest-activity rhythm in humans, the use of these parameters in animals has been described in the literature in rats [ 68 ], mice [ 69 ], and marmosets [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%